2022
DOI: 10.3390/agronomy12081874
|View full text |Cite
|
Sign up to set email alerts
|

Genotype Variations in Water Use Efficiency Correspond with Photosynthetic Traits in Tempranillo Grapevine Clones

Abstract: Mediterranean viticulture is highly dependent on soil water availability. Moreover, global warming is likely to increase average temperatures and the frequency of heat waves, thus leading to greater water scarcity. To cope with this situation, much research focused on the selection of genotypes with higher water use efficiency (WUE). Several previous studies indicated that WUE varies between genotypes of the Tempranillo cultivar with some showing interesting improvement in the leaf WUE. Here, we assessed the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 59 publications
2
7
0
Order By: Relevance
“…Notwithstanding, the environment has also been a relevant factor. These results are in agreement with those observed in “Tempranillo”, in which, despite the inter-seasonal variability, consistency in the WUE response of genotypes to water deficit has also been detected across environments [ 17 , 18 , 19 ].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Notwithstanding, the environment has also been a relevant factor. These results are in agreement with those observed in “Tempranillo”, in which, despite the inter-seasonal variability, consistency in the WUE response of genotypes to water deficit has also been detected across environments [ 17 , 18 , 19 ].…”
Section: Discussionsupporting
confidence: 92%
“…In fact, Dayer et al [ 14 ] observed that the capacity of genotypes to increase water use under well-watered conditions was strongly associated with hydraulic traits. However, Tortosa et al [ 19 ] did not report differences in leaf hydraulic traits (osmotic potential at turgor loss point, cell wall elasticity, or cell capacitance) that would explain differences in gas exchange parameters (g s and WUE i ) among “Tempranillo” genotypes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations